Identifying factors influencing women academics in STEM careers: evidence from a Latin American country - Avolio, B.; Chávez, J.M. (Emerald Publishing, 2024)
Purpose This phenomenological study, conducted within the discourse on the underrepresentation of women in academia, examined the factors influencing the advancement of women academics in science, technology, engineering, and mathematics (STEM). Design/methodology/approach The sample comprised twenty-one women academics from both public and private universities in Peru. Data were collected through in-depth interviews based on the women's experiences and subsequently processed using Moustakas’ (1994) stages for encoding, categorization, and analysis. Findings The study introduces a conceptual framework of nine factors – personal tastes and preferences, attitudes towards science as a vocation, care work, work–life balance, congruent gender roles, occupational segregation, lack of opportunities, low salaries, and lack of gender equality policies – that impact the career progression of women in STEM fields. Originality/value The results offer valuable insights for policymakers and academic authorities to address the barriers affecting women academics in STEM. The uniqueness of this paper lies in its investigation in Peru, a country with the highest female labor force participation in Latin America, where women constitute the majority of undergraduate program graduates.
Keywords: Latin Americans; Career development; Higher education; Demographic economics; Political science; Psychology; Economic growth; Pedagogy; Sociology; Economics; https://purl.org/pe-repo/ocde/ford#5.03.02